Beyond the Mosque: Diverse Spaces of Muslim Worship - Hussaini, Mehrullah (Islamic Studies Review, 2024)
Beyond the Mosque: Diverse Spaces of Muslim Worship (Rizwan Mawani) UK: I.B. Tauris, 2019, https://doi.org/10.56529/isr.v2i2.211